Ethene-1,1,2,2-tetracarbonitrile and Methanol in the Methylating Reaction of Tertiary Amines to the Quaternary Ammonium Compounds of 1,1-Dicyano-2-methoxy-2-oxoethane-1-ide - Sheverdov, Vladimir Р.; Davydova, Vera V.; Nasakin, Oleg E.; Mar’yasov, Maksim A.; Lodochnikova, Olga A. (Synlett, 2019)
We discovered a new method to methylate tertiary amines such as urotropine, triethylamine, pyridine, 2-methylpyridine, 4-acetylpyridine, and isonicotinamide, up to quaternary ammonium compounds, with 1,1-dicyano-2-methoxy-2-oxoethane-1-ide being the counterion. Methyl-1,3,5,7-tetraazaadamantan-1-ium 1,1-dicyano-2-methoxy-2-oxoethane-1-ide, N,N-diethyl-N-methylethanaminium 1,1-dicyano-2-methoxy-2-oxoethane-1-ide, and substituted-methylpyridinium 1,1-dicyano-2-methoxy-2-oxoethane-1-ides were synthesized. Quaternary ammonium compounds of 1,1-dicyano-2-methoxy-2-oxothane-1-ide were synthesized within a single stage by stirring methanol solutions of tertiary amines with ethene-1,1,2,2-tetracarbonitrile (ETCN) at room temperature. In the reaction of ETCN with tertiary amines in methanol, processes occur that form the 1,1-dicyano-2-methoxy-2-oxoethane-1-ide fragment with simultaneous N-methylation. Crystal structures based on X-ray diffraction analysis of the obtained compounds were studied.
Keywords: methylation; ethene-1,1,2,2-tetracarbonitrile; 1,1-dicyano-2-methoxy-2-oxoethane-1-ide; methanol; tertiary amines